The Effectiveness of Ariel Noah’s Influencer Marketing Strategy on Brand Awareness in the Fashion Industry of 3Second - Abdul Majid, Fikih; Kusmana, Givanisa; Rahma Fitriati, Lisna; Narda Anargya, Layra; Shalahudin Al-Ayyubi, Muhammad; Hermawan, Adam (International Conference on Digital Business Innovation and Technology Management (ICONBIT), 2024)
The development of digital technology and social media in recent years has triggered major changes in marketing strategies, especially in the fashion industry. Influencer marketing has become one of the popular strategies, where brands work with influential individuals to promote their products. This study aims to analyze the effectiveness of the influencer marketing campaign carried out by Ariel Noah in increasing brand awareness of the fashion brand 3Second. The study used a quantitative approach with an explanatory design. The sample of this study was 100 consumers aged 18-34 years who were active on social media platforms such as Instagram and TikTok, and had seen relevant campaigns in the last 3 months. Data were collected through a closed questionnaire with a Likert scale and analyzed using simple linear regression to test the relationship between influencer marketing strategies and brand awareness. In conclusion, the use of influencers such as Ariel Noah’s has proven effective in building brand awareness among consumers, especially millennials and Gen Z who are more responsive to personal and authentic content than conventional advertising.